Impalement Injury to The Heart - Pradhan, S; Sapkota, R; Shrestha, U K; Amatya, R; Koirala, B (Kathmandu University Medical Journal, 2012)
Cardiac impalement injury is rare and one of the most severe penetrating chest injuries, often fatal. The management of penetrating cardiac injuries is a challenging one. The success in management of impaling cardiac trauma requires stabilization of the impaling object, expeditious transfer to a facility for open heart surgery, rapid imaging, access to blood and blood products and a ready surgical team. We report a case of impalement injury to the heart by a stick, transfixing the right ventricle and its successful treatment. http://dx.doi.org/10.3126/kumj.v9i1.6270 Kathmandu Univ Med J 2011;9(1):80-2